Directors’ Liability of PT Pertamina Patra Niaga for Uncompensated Financial Burdens Arising from Government-Mandated Assignments in the Supply and Distribution of Petroleum Fuels - Evalina Sitepu; Mailinda Eka Yuniza (Jurnal Hukum Indonesia, 2026)
This research examines the liability of the Board of Directors of State-Owned Enterprises for financial burdens arising from Government assignments in the supply and distribution of fuel oil that are not fully compensated by the Government. This research aims to analyse the extent to which such financial burdens may affect the accountability of the Board of Directors in managing the company. This research employs a normative-empirical legal method with a juridical-analytical approach. The normative approach was conducted through the examination of laws and regulations, legal documents, and relevant legal doctrines, while the empirical approach is carried out through document analysis and interviews with relevant stakeholders. The results of this study show that losses or under-recovery arising from Government assignments cannot automatically be attributed to the personal liability of the Board of Directors. Directors’ liability may arise only if fault or negligence in corporate management is proven. Therefore, the liability of the Board of Directors must be assessed based on the source of risk and the quality of management, rather than merely on the existence of corporate losses.